Development of Application for Early Intervention Speech Therapy in Children with Intellectual Disability - Niratama, Fairus; Wagino, Wagino; Widajati, Wiwik; Andajani, Sri Joeda (Department of Special Education, 2023)
This study aims to describe the stages of the speech therapy application development process. This research produces an android application product that can be used in early intervention in speech therapy for children with intellectual disabilities. This development research is based on the development method of Gall, et al. (2007), and only carried out up to five stages, namely: 1) Research and information collecting (searching and collecting data), 2) Planning, 3) Develop preliminary form of product, 4) Preliminary field testing, 5) Main product revision. The data collection method in the form of a Likert scale was used in this study. Media validation was carried out by speech therapy content experts and media experts. The validation results from content experts obtained a score with a percentage of 88 percent and validation from media experts obtained a score of 93 percent. This indicates a very valid category, and this application is declared feasible and can be used. The results of the implementation for children with intellectual disabilities by giving a questionnaire obtained a percentage of 85 percent. So it can be concluded that the speech therapy application media is well used.Development of Application for Early Intervention Speech Therapy in Children with Intellectual Disability